2015
DOI: 10.4034/pboci.2015.151.42
|View full text |Cite
|
Sign up to set email alerts
|

Dental Avulsion: Are the Dentist Prepared to the Correct Management?

Abstract: Objective: To evaluate the knowledge of dentists from the health units (HU) of Porto Alegre -Brazil, regarding the management of avulsion of permanent teeth. Material and Methods: All dentists (n = 117) from HU were invited to answer a self-applied questionnaire regarding the treatment and preservation of avulsed permanent teeth in different clinical scenarios, based on the guidelines of the International Association of Dental Trauma (IADT). The professional data were also collected. The correlation between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For this reason, the level of knowledge and experience of general dentists, and therefore the training they have received in the past, is critical to the treatment of dental injuries in children. However, studies have shown that the knowledge of trauma and treatment management of general dentists may be inadequate [10][11][12][13][14]. The confrontation of general dentists with a limited number of patients with TDI may prevent them from maintaining and improving their knowledge level and experience [15].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the level of knowledge and experience of general dentists, and therefore the training they have received in the past, is critical to the treatment of dental injuries in children. However, studies have shown that the knowledge of trauma and treatment management of general dentists may be inadequate [10][11][12][13][14]. The confrontation of general dentists with a limited number of patients with TDI may prevent them from maintaining and improving their knowledge level and experience [15].…”
Section: Introductionmentioning
confidence: 99%